2020
DOI: 10.3390/microorganisms8030411
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Gut Microbial Diversity are Driven by Drug Use and Drug Cessation by Either Compulsory Detention or Methadone Maintenance Treatment

Abstract: In this work, we investigate differences in gut microbial diversity driven by drug use or by the widely used methods for drug cessation: methadone maintenance treatment (MMT) and compulsory detention (CD). Methods: 99 participants (28 CD participants, 16 MMT patients, 27 drug users, and 28 healthy controls) were selected using strict inclusion criteria. Nutritional intake and gut microbial diversity were analyzed with bioinformatics tools and SPSS 20.0. Results: Alpha diversity was not significantly different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…To avoid any geographic bias, study participants from different ethnic groups were all recruited from the same city of Lanzhou (Gansu, China). Previous studies have reported that gut microbiota can be influenced by environment, host genetic background and ethnicity, drug intake, diet, and dietary behavior ( Lloyd-Price et al, 2016 ; Gupta et al, 2017 ; Liao et al, 2018 ; Li et al, 2020 ; Liu et al, 2020 ). Zeb et al (2020) reported that time-restricted feeding could regulate circadian rhythms associated with modulation of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid any geographic bias, study participants from different ethnic groups were all recruited from the same city of Lanzhou (Gansu, China). Previous studies have reported that gut microbiota can be influenced by environment, host genetic background and ethnicity, drug intake, diet, and dietary behavior ( Lloyd-Price et al, 2016 ; Gupta et al, 2017 ; Liao et al, 2018 ; Li et al, 2020 ; Liu et al, 2020 ). Zeb et al (2020) reported that time-restricted feeding could regulate circadian rhythms associated with modulation of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies investigating the effects of chronic opioid use on the gut microbiome are limited [36][37][38][39][40] with conflicting results, as some report an increase in microbial diversity, 39,40 while others showed no significant changes in α diversity, 37 yet changes in microbial composition are consistent across these studies. [36][37][38][39] Principal coordinate analysis of our results reveals distinct differences in the microbiome of methadone-treated individuals, particularly in the second dimension. These differences are further highlighted by a decrease in evenness and richness in the α diversity of this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In line with diversity analyses, we observed a significant increase in the Bifidobacterium genus (Actinobacteria phylum) in methadone-treated individuals, which is consistent with the existing opioid literature. [36][37][38][39] Bifidobacterium, a highly represented genera in the adult microbiota, [41][42][43][44][45] is known to produce the SCFA acetate. 45 Interestingly, we observed a decrease in the content of fecal acetate and a positive correlation between Actinobacteria and fecal acetate.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 177 school-age children were enrolled and 67 children (26 zinc-deficient participants and 41 control participants) were chosen to explore the gut microbial community using amplicon sequencing according to the selection criteria [ 35 ], which included: (1) no history of acute or chronic illness (cancer, malignant tumors, kidney disease, heart disease, diabetes, liver disease, etc. ); (2) no gastrointestinal symptoms (constipation, diarrhea, etc.)…”
Section: Methodsmentioning
confidence: 99%